The Effect of Using‏‏Technology-Enhanced English Course (TEEC) in‏‏Teaching English as ‎a‏‏Foreign‏‏Language at Preparatory Schools - Madhloom Hashim ALI, Nadhim (International Journal of Psychosocial Rehabilitation, 2025)
This study aims to explore the impact of the Technology-Enhanced English Course (TEEC) in teaching English as a foreign language at Iraqi preparatory schools. The TEEC is a notable trend that integrates learning and teaching by combining traditional teaching methods with authentic materials. Teachers are consistently enabled to modify their teaching methods through the use of technology, which enables students to assume responsibility for learning in the target language. The sample was randomly selected and consisted of 44 enrolled English teachers to collect the necessary information. The findings showed that the majority of diverse teachers highlighted the significance of technology based on active learning in the classroom teaching of English as a foreign language. Implementing fresh information to enhance student engagement in the target language. The difference between traditional teaching and the technology-enhanced course was therefore significant at the p<0.05 level. The independent sample t-test shows that scores are significantly higher for technology teaching (M=3.45, SD=.474) than for traditional teaching (M=2.40, SD=.578), t(86)=5.92, sig=.000, p<0.05. Besides, there is no correlation between the traditional teaching method and teacher performance scores (X²=16.13, df 20, sig=.708, p<0.05). Nevertheless, a very strong positive association exists between technology teaching methods and teacher performance scores (X²=77.81, df 19, sig=.000, p<0.05). The study highlights the vital significance of TEEC in improving the quality of the learning process. This is accomplished by employing interactive learning-based technology teaching aids to facilitate the mastery of a foreign language.